Biological composite liquid material capable of releasing negative oxygen ions as well as preparation method and application of biological composite liquid material
By developing a biocomposite liquid material containing plant extracts, silver ion solutions and other components, the problems of low release amount, poor stability and high cost in the prior art are solved, and efficient, stable and low-cost negative oxygen ions are achieved Release, suitable for multiple application areas.
Patent Information
- Application Number
- CN202411531552.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-02-14
AI Technical Summary
The existing products that release negative oxygen ions have problems such as low release amount, poor stability and high cost, and it is difficult to meet the needs of high efficiency, stability and low cost.
Develop a biocomposite liquid material to promote oxygen molecules in the air through different mechanisms through the combination of specific amounts of plant extracts, silver ion solutions, titanium dioxide, nanosilica liquids, sodium oxide, magnesium oxide dispersions and other substances. Free electrons form negative oxygen ions and continue to be released.
It has achieved efficient, continuous, environmentally friendly and controllable negative oxygen ion release, with good stability and safety, and is suitable for air purification, health care and building materials and other fields.
Smart Images

Figure BDA0005110590770000111 
Figure BDA0005110590770000112 
Figure BDA0005110590770000113
Abstract
Description
Technical Field
[0001] The embodiments of the present invention relate to the field of material technology, and specifically to a biocomposite liquid material capable of releasing negative oxygen ions, and a preparation method and application thereof. Background Art
[0002] As people's living standards improve and they pay more attention to health, the requirements for air quality are getting higher and higher. Negative oxygen ions are known as "air vitamins" and have many benefits for human health, such as improving sleep, enhancing immunity, and relieving fatigue. At present, there are some products that release negative oxygen ions on the market, such as negative ion generators and tourmaline, but these products have problems such as low release, poor stability, and high cost. Therefore, it is of great practical significance to develop a new material that releases negative oxygen ions efficiently, stably, and at low cost. Summary of the invention
[0003] To this end, an embodiment of the present invention provides a biocomposite liquid material that can release negative oxygen ions, and a preparation method and application thereof. The biocomposite liquid material has the characteristics of efficiently releasing negative oxygen ions, and is safe and reliable, and can be widely used in air purification, medical care, building materials and other fields.
[0004] In order to achieve the above purpose, the embodiment of the present invention provides the following technical solutions:
[0005] According to a first aspect of an embodiment of the present invention, the present invention provides a biocomposite liquid material, characterized in that, measured by weight, the biocomposite liquid material comprises: 12-18 parts of plant extract, 1-4 parts of silver ion solution, 2-5 parts of titanium dioxide, 10-15 parts of nano-silicon dioxide liquid, 2-8 parts of sodium oxide, 1-6 parts of magnesium oxide dispersion, 0.5-1.5 parts of calcium hydroxide solution, 1-3 parts of ferric oxide colloidal solution, 2-6 parts of zinc oxide dispersion, 12-18 parts of mixed silica sol, 15-20 parts of nano-borosilicate liquid material, 0.5-1.5 parts of surfactant, 4-8 parts of glycerol, and 10-15 parts of deionized water.
[0006] The generation of negative oxygen ions is related to the ionization ability of the substance, the photocatalytic activity and the interaction with water molecules. The present invention uses a specific amount of the above substances as raw materials, and promotes oxygen molecules in the air to capture free electrons through different mechanisms to form negative oxygen ions and continuously release them, which has the advantages of high efficiency, sustainability, environmental protection and controllability.
[0007] Furthermore, the biocomposite liquid material includes: 15 parts of plant extract, 2 parts of silver ion solution, 3 parts of titanium dioxide, 12 parts of nano-silicon dioxide liquid, 6 parts of sodium oxide, 5 parts of magnesium oxide dispersion, 1 part of calcium hydroxide solution, 2 parts of ferric oxide colloidal solution, 4 parts of zinc oxide dispersion, 15 parts of mixed silica sol, 16 parts of nano-borosilicate liquid material, 1 part of surfactant, 6 parts of glycerol, and 12 parts of deionized water.
[0008] Furthermore, the preparation method of the plant extract comprises the following steps:
[0009] (1) using pine needles of Pinus armandii with an age of more than 10 years, washing them until there are no suspended particles, drying them at 140-160° C. and crushing them into 60-100 meshes;
[0010] (2) adding the crushed pine needles to 45-60% ethanol at a mass volume ratio of 15-50 g / ml, soaking for 120-160 minutes, and then placing them under 450-500 MPa for 60-90 minutes and then quickly releasing the pressure, and continuously pressurizing and releasing the pressure 2-3 times to obtain an extract;
[0011] (3) filtering, concentrating the obtained filtrate under reduced pressure, and spray drying to obtain a yellow powdery pine needle extract;
[0012] (4) Add pine needle extract to deionized water at a mass ratio of 1:1-1.5, let stand for 30-45 minutes, mix in a closed container at a speed of 1000 rpm for 30 minutes, pour out and let stand to cool to room temperature, pass through a 700-mesh biofiber filter and decolorize with activated carbon with an iodine value of 1200 to obtain a nearly colorless solution, which is placed in a closed container for later use.
[0013] Furthermore, the mass fraction concentration of the silver ion solution is 0.4-0.6%;
[0014] The preparation method of the nano-silicon dioxide liquid comprises: introducing carbon dioxide gas at a flow rate of 2.5-3 liters / min into a liquid sodium silicate solution with a concentration of 15-16%, stirring for 150-180 minutes at room temperature and a speed of 100-150 revolutions / min, filtering the obtained reaction liquid through a 500-mesh biofiber filter and an ultrafiltration membrane with a particle size of 100 nanometers in sequence to obtain the nano-silicon dioxide liquid.
[0015] Further, the concentration of the magnesium oxide dispersion is 30-32% and the particle size is 40 nm;
[0016] The preparation method of the calcium hydroxide solution comprises: drying quicklime to a moisture content of less than 10%, repeatedly grinding and sieving to 300 meshes, adding deionized water at a mass ratio of 1:5, stirring at 1500-2000 rpm for 30-45 minutes, filtering other materials through a 650-mesh nylon filter, and preparing a calcium hydroxide solution;
[0017] The concentration of the ferric oxide colloidal solution is 30-40%;
[0018] The zinc oxide dispersion has a concentration of 10%, a pH value of 8-9, and a particle size of 100 nm;
[0019] The surfactant is an amino acid ester type surfactant.
[0020] Furthermore, the preparation method of the mixed silica sol includes: mixing alkaline silica sol with a pH of 7.5-8.5 and a silica particle size of less than 100 nanometers and silica sol with a metal particle size of more than 100 nanometers in a mass ratio of 1:1, stirring at 2000-2500 rpm for 45-60 minutes, pouring out and standing to cool to room temperature, selecting a nano-scale ultrafiltration membrane with a membrane diameter of 100 nanometers for filtering, and obtaining a mixed silica sol.
[0021] Furthermore, the preparation method of the nano borosilicate liquid material is as follows: tourmaline ore powder is put into deionized water at a mass ratio of 1:2, stirred at a speed of 50-60 rpm for 18-24 hours, and then filtered through a biofiber filter with a particle size of 100 nanometers, and a membrane filter with a pH adjusted to 7.2-7.8 and a membrane diameter of 100 nanometers to obtain a nano borosilicate liquid material.
[0022] According to a second aspect of an embodiment of the present invention, the present invention provides a method for preparing a biocomposite liquid material capable of releasing negative oxygen ions as described in any one of the above items, the method comprising:
[0023] Take part of the deionized water and place it in a fixed stirrer, adjust the speed to 200-300 rpm, add silver ion solution, titanium dioxide, magnesium oxide dispersion, sodium oxide, calcium hydroxide solution, ferric oxide colloidal solution, mixed silica sol, nano borosilicate liquid material, glycerol in sequence, and stir for 30 min-45;
[0024] Then add nano-silicon dioxide liquid, zinc oxide dispersion, and surfactant in sequence, and stir for 45-60 minutes;
[0025] Then, the plant extract and the remaining deionized water are added in sequence and stirred for 60-90 minutes to obtain the biocomposite liquid material.
[0026] Furthermore, the partial deionized water is 40-60% of the mass of the deionized water.
[0027] According to a third aspect of the embodiments of the present invention, the present invention provides the use of the above-mentioned biocomposite liquid material capable of releasing negative oxygen ions in air purification, medical care, and building materials. Specifically:
[0028] 1. Air purification
[0029] Indoor air purification
[0030] Spraying new bio-composite liquid materials on indoor walls, ceilings, furniture and other surfaces can effectively remove harmful gases such as formaldehyde, benzene, TVOC, etc. in the indoor air, while releasing a large amount of negative oxygen ions to improve indoor air quality.
[0031] Car air purification
[0032] Spraying the new bio-composite liquid material on the surface of car interior can effectively remove odors and harmful gases in the car, while releasing negative oxygen ions to improve the air quality in the car.
[0033] 2. Medical care
[0034] Negative oxygen ion therapy
[0035] Applying new bio-composite liquid materials to negative oxygen ion therapy can improve the physiological functions of the human body by inhaling negative oxygen ions, such as enhancing immunity, relieving fatigue, and improving sleep.
[0036] Medical Devices
[0037] Applying new biocomposite liquid materials to medical equipment, such as oxygen concentrators, air purifiers, air conditioners, etc., can improve the performance and effectiveness of the equipment.
[0038] (III) Building materials
[0039] coating
[0040] By adding new bio-composite liquid materials to coatings, environmentally friendly coatings with the function of releasing negative oxygen ions can be prepared. They can be used for interior and exterior wall decoration of buildings to improve indoor and outdoor air quality.
[0041] Wall cloth, wallpaper and other building exterior
[0042] The new bio-composite liquid material is added to the exterior of buildings such as wall coverings, wallpapers, lime walls, etc. After coming into contact with the air, it has the function of releasing negative oxygen ions, thereby improving indoor air quality.
[0043] floor
[0044] By adding new bio-composite liquid materials to the floor, an environmentally friendly floor with the function of releasing negative oxygen ions can be prepared. It can be used for indoor floor decoration and improve indoor air quality.
[0045] The embodiments of the present invention have the following advantages:
[0046] The biocomposite liquid material of the present invention is prepared from a variety of natural biomaterials through a specific process, has the characteristic of efficiently releasing negative oxygen ions, and can effectively improve air quality; it has good stability, can be stored for about 3 years at room temperature, and is easy to use; it is non-toxic, non-irritating, safe and reliable to the human body, and can be widely used in air purification, medical care, building materials and other fields, and has broad market prospects. DETAILED DESCRIPTION
[0047] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] In the following content, the preparation method or source of each raw material is introduced as follows:
[0049] 1. The preparation method of plant extract is as follows:
[0050] (1) Use pine needles (pine hairs) of 10 years or older, wash them until there are no suspended particles, dry them at 150°C and crush them into 100 mesh.
[0051] (2) Solvent soaking: Put the crushed pine needles into a polyethylene bag, add 45% ethanol solvent at a mass volume ratio of 15-50g / ml, seal the bag, and soak for 120 minutes.
[0052] (3) Ultrahigh pressure treatment: Place the polyethylene bag containing the pine needle raw material into an ultrahigh pressure container, apply 450 MPa ultrahigh pressure and maintain the pressure for 60 minutes, then quickly release the pressure. Repeat the pressurization and pressure release treatment twice.
[0053] (4) Treatment 1: After the extraction is completed, the extract is filtered through 500 mesh to remove the residue; the filtrate is introduced into a concentrator for reduced pressure concentration (temperature controlled at 50°C, vacuum degree 0.06-0.1MPa) and the ethanol solvent is recovered to obtain a colloid-like yellow-brown pine needle extract; further spray drying is performed to obtain a yellow powdery pine needle extract.
[0054] (5) Treatment 2: Add pine needle extract to deionized water at a mass ratio of 1:1, stand at 30°C, and after fully dissolved, mix in a high-speed mixer at a speed of 1000 revolutions per minute for 30 minutes, pour out and stand to cool to room temperature. Pass through a 700-mesh biofiber filter to obtain a 60% light yellow filtrate, then decolorize it with activated carbon with an iodine value of 1200 to a nearly colorless solution, and put it into a sealed container for use.
[0055] 2. Silver ion solution
[0056] Preparation of silver ion solution using electrolysis:
[0057] (1) A graphite carbon rod is used as the anode, a silver rod is used as the cathode (the purity of the silver rod is above 99%), and the distance between the electrodes is 5 cm. Ultrapure water is used as the solvent.
[0058] (2) Electrolysis is usually performed using a 36 V DC voltage with a current density of 0.5-0.6 A / dm 2 , electrolysis is carried out at room temperature, and the solution is stirred at a speed of 200 revolutions per minute during the electrolysis process.
[0059] (3) After the electrolysis is completed, the anion concentration is detected and the silver ion concentration is adjusted to about 0.5% (mass fraction).
[0060] 3. Titanium dioxide
[0061] Purchase 650 mesh rutile titanium dioxide from the market.
[0062] 4. Nano-silicon dioxide liquid
[0063] The carbon dioxide precipitation method is used to prepare nano-silicon dioxide liquid, and the preparation method is as follows:
[0064] (1) Raw materials: liquid sodium silicate solution, concentration is 15%. Carbon dioxide gas, with high purity is required to ensure the smooth progress of the reaction.
[0065] (2) Process: Place a liquid sodium silicate solution in a reaction vessel and stir at a speed of 100 revolutions per minute. While stirring, introduce carbon dioxide gas at a rate of 2.5 liters per minute. Carbon dioxide reacts with sodium silicate to produce silicic acid and sodium carbonate. The introduction speed and flow rate of carbon dioxide need to be controlled during the reaction. The reaction temperature is carried out at room temperature and the reaction time is 180 minutes.
[0066] (3) Post-reaction treatment: After the reaction is completed, the first filtration is performed at room temperature using a 500-mesh biofiber filter to remove other substances and obtain a colorless and transparent nano-silica liquid. The second filtration is performed using a nano-scale ultrafiltration membrane with a membrane diameter of 100 nanometers.
[0067] (4) Slowly pour the nano-silicon dioxide liquid into the ultrafilter and evenly and completely distribute it on the ultrafiltration membrane. Natural gravity filters out other substances smaller than 100 nanometers and removes them in time. The high-purity nano-silicon dioxide liquid is stored in a sealed container for future use.
[0068] 5. Sodium oxide
[0069] Purchased from the market, 80% purity, 650 mesh, white powder.
[0070] 6. Magnesium oxide dispersion
[0071] Nano magnesium oxide dispersion is purchased from the market, with a particle size of 40 nanometers and a content of 30%.
[0072] 7. Calcium hydroxide solution
[0073] Preparation: Pure white quicklime is heated and dried to a moisture content of less than 10%, repeatedly ground and sieved to 300 mesh, deionized water is added in a ratio of 1:5 and stirred at high speed for 30 minutes at a speed of 2000 revolutions per minute, and other materials are filtered out through a 650-mesh nylon filter to prepare a calcium hydroxide solution, which is then placed in a sealed container and sealed for storage.
[0074] 8. Ferric oxide colloidal solution (catalyst)
[0075] Purchase 30-40% light red ferric oxide colloidal solution from the market.
[0076] 9. Zinc oxide dispersion
[0077] The zinc oxide dispersion is purchased from the market as a white liquid with a concentration of 10%, a pH value of 8-9, and a particle size of 100 nanometers.
[0078] 10. Mixed silica sol (colloid diameter 100 nanometers)
[0079] The preparation method is as follows:
[0080] (1) Alkaline silica sol (pH 7.5-8.5, silica particle size less than 100 nanometers) purchased from the market and high-purity silica sol (metal particle size greater than 100 nanometers) were mixed at a mass ratio of 1:1, and the mixture was mixed in a closed manner in a high-speed mixer at a speed of 2000 revolutions per minute for 60 minutes, and then poured out and allowed to stand and cool to room temperature for use.
[0081] (2) Filtration by room temperature ultrafiltration: The nano-scale ultrafiltration membrane has a membrane diameter of 100 nanometers.
[0082] (3) The silica sol mixture after high-speed mixing is slowly poured into the ultrafilter, evenly and completely distributed on the ultrafiltration membrane, and other substances smaller than 100 nanometers in the mixed silica sol are filtered out by natural gravity and removed in time, and the mixed silica sol is obtained and stored in a sealed container for later use.
[0083] 11. Nano borosilicate liquid material
[0084] Materials: Choose high-quality tourmaline powder with a particle size greater than 200 mesh, and use deionized water at a dosage of 1:15 times.
[0085] The preparation process is as follows:
[0086] (1) Secondary crushing of tourmaline: Heat 200-mesh tourmaline powder at 300°C and dry it to a moisture content of less than 5%, cool it to 50°C and put it into a high-speed crusher for 90 minutes. Let it stand and cool to below 40°C before sieving it. Use microwave vibration to separate 500-mesh powder and remove large particles.
[0087] (2) The 500-mesh tourmaline ore powder after crushing was put into deionized water at a mass ratio of 1:2, and the mixture was fully soaked for 24 hours. The mixture was stirred at a speed of 50 revolutions per minute to improve the dissolution speed and uniformity.
[0088] (3) After soaking, the soaking liquid is filtered using a biofiber filter with a particle size of 100 nanometers to remove particles and impurities.
[0089] (4) Adjust the pH to around 7.5 using an acidic (hydrochloric acid) or alkaline (sodium hydroxide) solution.
[0090] (5) Secondary filtration: The adjusted tourmaline solution is filtered using a nano-membrane filter (membrane diameter of 100 nanometers) to remove impurities for the second time, and the prepared nano-borosilicate liquid material is placed in a sealed container for storage for later use.
[0091] 12. Surfactants
[0092] Purchase amino acid ester surfactants from the market.
[0093] 13. Glycerin
[0094] Industrial grade (first level) liquid glycerin is purchased from the market, with a glycerin content greater than 98.5%, a transparent appearance, no suspended matter, and no odor.
[0095] 14. Deionized water
[0096] The conductivity purchased on the market is usually 1μS / cm and the pH value is around 7.
[0097] Example 1
[0098] The present embodiment provides a biocomposite liquid material that can release negative oxygen ions, and its raw materials are: 15Kg of plant extract, 2Kg of silver ion solution, 3Kg of titanium dioxide, 12Kg of nano-silicon dioxide liquid, 6Kg of sodium oxide, 5Kg of magnesium oxide dispersion, 1Kg of calcium hydroxide solution, 2Kg of ferric oxide colloidal solution, 4Kg of zinc oxide dispersion, 15Kg of mixed silica sol, 16Kg of nano-borosilicate liquid material, 1Kg of surfactant, 6Kg of glycerol, and 12Kg of deionized water.
[0099] The method for preparing the above-mentioned biocomposite liquid material comprises the following steps:
[0100] (1) Preparation: high pressure reactor with a capacity of 150 liters, adjustable ultra-high pressure greater than 500 MPa, fixed adjustable agitator with a speed greater than 2000 rpm, portable agitator with a speed greater than 1000 rpm, bio-fiber and membrane filters with a particle size less than 100 nanometers, timer, and 100-liter clean sealable container.
[0101] (2) Preparation process
[0102] (3) 6 kg of deionized water was placed in a fixed agitator, and the agitator was started and the speed was adjusted to 200 rpm. 2 kg of silver ion solution, 3 kg of titanium dioxide, 5 kg of magnesium oxide dispersion, 6 kg of sodium oxide, 1 kg of calcium hydroxide solution, 2 kg of ferric oxide colloidal solution, 15 kg of mixed silica sol, 16 kg of nano borosilicate liquid material, and 6 kg of glycerol were placed in the agitator in order. The agitation time was 30 minutes.
[0103] (4) After 30 minutes of low-speed stirring, the speed was adjusted to 1500 rpm and the stirring time was 90 minutes.
[0104] (5) After 90 minutes of high-speed stirring, stop the machine and let it stand to cool down to less than 50°C.
[0105] (6) The speed was adjusted to 200 rpm, and then 12 kg of nano-silicon dioxide liquid, 4 kg of zinc oxide dispersion, and 1 kg of surfactant were placed in the agitator in sequence, totaling 17 kg, and the agitation time was 45 minutes.
[0106] (7) After 45 minutes of low-speed stirring, the speed was adjusted to 1500 rpm, the stirring time was 120 minutes, the machine was stopped, and the temperature was allowed to cool to below 50°C.
[0107] (8) The speed was adjusted to 200 rpm, and 15 kg of plant extract and the remaining 6 kg of deionized water were added in sequence. A total of 21 kg was placed into the stirrer and stirred for 60 minutes.
[0108] (9) After 60 minutes of low-speed stirring, adjust the speed to 1500 rpm and the stirring time to 150 minutes. Stop the machine and let it stand to cool down to less than 50°C.
[0109] (10) The first filtration uses a 100 nanometer biofiber filter to remove particles larger than 100 nanometers.
[0110] (11) First decolorization and odor removal: Filter twice with activated carbon with an iodine value of 1200 to obtain a colorless, odorless, transparent solution.
[0111] (12) Place the above solution into a reaction kettle and stir it with a mobile stirrer for 20 minutes at a speed of 200 rpm. Allow to stand at room temperature for 30 minutes.
[0112] (13) The reactor was sealed, pressurized to 450 MPa, and allowed to stand for 6 hours to fully dissolve.
[0113] (14) Second decolorization and odor removal: Filter twice with activated carbon with an iodine value of 1200 to obtain a colorless, odorless, transparent solution.
[0114] (15) The second filtration uses a 100-nanometer membrane filter to remove particles larger than 100 nanometers, producing a high-purity, colorless, odorless, and transparent new biocomposite liquid material.
[0115] (16) Place part of the high-purity biocomposite liquid and deionized water in a mass ratio of 1:3 into a high-speed mixer, adjust the speed to 1500 rpm, and stir for 150 minutes. Stop the mixer and let it stand to cool down to less than 50°C.
[0116] (17) The above solution was placed in a reactor and allowed to stand at room temperature for 30 minutes. The reactor was sealed and pressurized to 450 MPa and allowed to stand for 6 hours to fully dissolve.
[0117] (18) The third filtration uses a 100 nanometer membrane filter to remove particles larger than 100 nanometers, and obtains a standard biocomposite liquid new material, which is sealed and stored in a prepared container for later use.
[0118] Example 2
[0119] The present embodiment provides a biocomposite liquid material that can release negative oxygen ions, and its raw materials are: 12Kg of plant extract, 3Kg of silver ion solution, 4Kg of titanium dioxide, 10Kg of nano-silicon dioxide liquid, 7Kg of sodium oxide, 2Kg of magnesium oxide dispersion, 1Kg of calcium hydroxide solution, 1.2Kg of ferric oxide colloidal solution, 3Kg of zinc oxide dispersion, 17Kg of mixed silica sol, 18Kg of nano-borosilicate liquid material, 0.6Kg of surfactant, 7Kg of glycerol, and 15Kg of deionized water.
[0120] The preparation method of the above biocomposite liquid material is the same as that in Example 1.
[0121] Example 3
[0122] The present embodiment provides a biocomposite liquid material that can release negative oxygen ions, and its raw materials are: 17Kg of plant extract, 1.5Kg of silver ion solution, 2Kg of titanium dioxide, 15Kg of nano-silicon dioxide liquid, 4Kg of sodium oxide, 6Kg of magnesium oxide dispersion, 0.8Kg of calcium hydroxide solution, 1.5Kg of ferric oxide colloidal solution, 6Kg of zinc oxide dispersion, 12Kg of mixed silica sol, 16Kg of nano-borosilicate liquid material, 1Kg of surfactant, 7Kg of glycerol, and 10Kg of deionized water.
[0123] The preparation method of the above biocomposite liquid material is the same as that in Example 1.
[0124] Test Example 1
[0125] Performance Testing
[0126] (1) Negative air ion concentration
[0127] The biocomposite liquid material of Examples 1-3 (concentration of 20%, that is, the biocomposite liquid material stock solution and deionized water were mixed at a volume ratio of 2:8) was tested for air negative ion concentration. The results are shown in Table 1 below.
[0128] Table 1
[0129]
[0130]
[0131] The results show that the number of negative ions released by the biocomposite liquid material (20%) provided in the embodiment of the present invention is 10000-11810 / cm 3 , having excellent anion releasing ability, among which Example 1 is the best.
[0132] (2) Formaldehyde purification performance
[0133] The formaldehyde purification performance of the biocomposite liquid materials of Examples 1-3 (with a concentration of 20%) was tested. The results are shown in Table 2 below.
[0134] Table 2
[0135]
[0136] The results show that the biocomposite liquid material provided by the embodiments of the present invention has better formaldehyde removal performance, among which Example 1 reaches more than 97%, belonging to Class A formaldehyde removal product.
[0137] (3) Durability of formaldehyde removal
[0138] The formaldehyde removal durability test was performed on the biocomposite liquid materials of Examples 1-3. The results are shown in Table 3 below.
[0139] Table 3
[0140]
[0141] The results show that the biocomposite liquid material provided by the embodiments of the present invention has better formaldehyde removal durability, among which Example 1 reaches more than 93%, belonging to Class A formaldehyde removal products.
[0142] (4) Internal and external radiation index detection
[0143] The biocomposite liquid materials of Examples 1-3 were tested for internal and external radiation index. The results are shown in Table 4 below.
[0144] Table 4
[0145]
[0146] The results show that the internal and external radiation index of the biocomposite liquid material provided by the embodiment of the present invention is not detected, and it belongs to Class A standard product.
[0147] (5) Heavy metal detection
[0148] The biocomposite liquid materials (30% concentration) of Examples 1-3 were tested for harmful substance content according to GB / T18582. The results showed that no lead, mercury, chromium, cadmium, benzene, toluene, xylene, free formaldehyde, or volatile organic matter was detected in the materials of Examples 1-3.
[0149] (6) Negative oxygen ion release detection
[0150] The negative oxygen ion release of the biocomposite liquid materials of Examples 1-3 was tested using a negative oxygen ion detector. The results are shown in Table 5 below.
[0151] Table 5
[0152] sample <![CDATA[Negative oxygen ion release amount (pcs / cm 3 )]]> Example 1 9980 Example 2 8230 Example 3 5250
[0153] The test results show that the biocomposite liquid material of the present invention has a high negative oxygen ion release rate, which can reach 5000-10000 / cm 3 .
[0154] (7) Stability test
[0155] The biocomposite liquid material of Example 1 was used under different temperature and humidity conditions to observe its stability. The results are shown in Tables 6-7 below.
[0156] Table 6
[0157]
[0158] Table 7
[0159]
[0160] The stability test results of the biocomposite liquid materials of Examples 2-3 are not significantly different from those of Example 1. The above content shows that the biocomposite liquid novel material of the present invention has good stability.
[0161] (8) Safety testing
[0162] The biocomposite liquid materials of Examples 1-3 were subjected to safety tests such as acute toxicity test and skin irritation test.
[0163] The test results show that the biocomposite liquid material provided by the embodiment of the present invention is non-toxic, non-irritating, and safe and reliable to the human body.
[0164] Although the present invention has been described in detail above by general description and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements can be made to the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A biocomposite liquid material capable of releasing negative oxygen ions, characterized in that: The biocomposite liquid material comprises, by weight: 12-18 parts of plant extract, 1-4 parts of silver ion solution, 2-5 parts of titanium dioxide, 10-15 parts of nano silicon dioxide liquid, 2-8 parts of sodium oxide, 1-6 parts of magnesium oxide dispersion, 0.5-1.5 parts of calcium hydroxide solution, 1-3 parts of ferric oxide colloidal solution, 2-6 parts of zinc oxide dispersion, 12-18 parts of mixed silica sol, 15-20 parts of nano borosilicate liquid material, 0.5-1.5 parts of surfactant, 4-8 parts of glycerol and 10-15 parts of deionized water.
2. The biological composite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The biocomposite liquid material comprises: 15 parts of plant extract, 2 parts of silver ion solution, 3 parts of titanium dioxide, 12 parts of nano silicon dioxide liquid, 6 parts of sodium oxide, 5 parts of magnesium oxide dispersion, 1 part of calcium hydroxide solution, 2 parts of ferric oxide colloidal solution, 4 parts of zinc oxide dispersion, 15 parts of mixed silica sol, 16 parts of nano borosilicate liquid material, 1 part of surfactant, 6 parts of glycerol and 12 parts of deionized water.
3. The biocomposite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The preparation method of the plant extract comprises the following steps: (1) using pine needles of Pinus armandii with an age of more than 10 years, washing them until there are no suspended particles, drying them at 140-160° C. and crushing them into 60-100 meshes; (2) adding the crushed pine needles to 45-60% ethanol at a mass volume ratio of 15-50 g / ml, soaking for 120-160 minutes, and then placing them under 450-500 MPa for 60-90 minutes and then quickly releasing the pressure, and continuously pressurizing and releasing the pressure 2-3 times to obtain an extract; (3) filtering, concentrating the obtained filtrate under reduced pressure, and spray drying to obtain a yellow powdery pine needle extract; (4) Add pine needle extract to deionized water at a mass ratio of 1:1-1.5, let stand for 30-45 minutes, mix in a closed container at a speed of 1000 rpm for 30 minutes, pour out and let stand to cool to room temperature, pass through a 700-mesh biofiber filter and decolorize with activated carbon with an iodine value of 1200 to obtain a nearly colorless solution, which is placed in a closed container for later use.
4. The biocomposite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The mass fraction concentration of the silver ion solution is 0.4-0.6%; The preparation method of the nano-silicon dioxide liquid comprises: introducing carbon dioxide gas at a flow rate of 2.5-3 liters / min into a liquid sodium silicate solution with a concentration of 15-16%, stirring for 150-180 minutes at room temperature and a speed of 100-150 revolutions / min, filtering the obtained reaction liquid through a 500-mesh biofiber filter and an ultrafiltration membrane with a particle size of 100 nanometers in sequence to obtain the nano-silicon dioxide liquid.
5. The biological composite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The concentration of the magnesium oxide dispersion is 30-32% and the particle size is 40 nm; The preparation method of the calcium hydroxide solution comprises: drying quicklime to a moisture content of less than 10%, repeatedly grinding and sieving to 300 meshes, adding deionized water at a mass ratio of 1:5, stirring at 1500-2000 rpm for 30-45 minutes, filtering other materials through a 650-mesh nylon filter, and preparing a calcium hydroxide solution; The concentration of the ferric oxide colloidal solution is 30-40%; The zinc oxide dispersion has a concentration of 10%, a pH value of 8-9, and a particle size of 100 nm; The surfactant is an amino acid ester type surfactant.
6. The biocomposite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The preparation method of the mixed silica sol comprises: mixing alkaline silica sol with a pH of 7.5-8.5 and a silica particle size of less than 100 nanometers and silica sol with a metal particle size of more than 100 nanometers in a mass ratio of 1:1, stirring at 2000-2500 rpm for 45-60 minutes, pouring out and cooling to room temperature, selecting a nano-scale ultrafiltration membrane with a membrane diameter of 100 nanometers for filtering, and obtaining a mixed silica sol.
7. The biocomposite liquid material capable of releasing negative oxygen ions according to claim 1, characterized in that: The preparation method of the nano borosilicate liquid material comprises: adding tourmaline ore powder into deionized water at a mass ratio of 1:2, stirring at a speed of 50-60 rpm for 18-24 hours, and then filtering through a biofiber filter with a particle size of 100 nanometers, and filtering through a membrane filter with a pH value adjusted to 7.2-7.8 and a membrane diameter of 100 nanometers in sequence to obtain the nano borosilicate liquid material.
8. The method for preparing the biocomposite liquid material capable of releasing negative oxygen ions according to any one of claims 1 to 7, characterized in that: The method comprises: Take part of the deionized water and place it in a fixed stirrer, adjust the speed to 200-300 rpm, add silver ion solution, titanium dioxide, magnesium oxide dispersion, sodium oxide, calcium hydroxide solution, ferric oxide colloidal solution, mixed silica sol, nano borosilicate liquid material, glycerol in sequence, and stir for 30 min-45; Then add nano-silicon dioxide liquid, zinc oxide dispersion, and surfactant in sequence, and stir for 45-60 minutes; Then, the plant extract and the remaining deionized water are added in sequence and stirred for 60-90 minutes to obtain the biocomposite liquid material.
9. The method for preparing a biological composite liquid material capable of releasing negative oxygen ions according to claim 8, characterized in that: The partial deionized water is 40-60% of the mass of the deionized water.
10. Application of the biocomposite liquid material capable of releasing negative oxygen ions as claimed in claim 1 in air purification, medical care and building materials.
Citation Information
Cited By
Herbal plant extract essence for releasing negative oxygen ions and extraction method thereof
CN120733093A
Herbal plant extract essence for releasing negative oxygen ions and extraction method thereof
CN120733093B
Negative oxygen ion spray and preparation method thereof
CN120919820A
Material capable of releasing negative oxygen ions and preparation method thereof
CN121045869A
Natural plant negative oxygen ion preparation rich in olefin and terpene substances and preparation method thereof
CN121198291A